Immuno-splenic Toxicity in Rats Fed with Dichlorvos-Treated Bean Diets - Amali, El-Khalid Onche Oinonyilokwu; Oche, Obochi Godwin; Benjamin, Anwhange Asen (Sahel Journal of Life Sciences FUDMA, 2024)
Dichlorvos an organophosphate compound is used in the agricultural sector for both pre-harvest and postharvest protection of crops. Large quantities are used globally every year with the developing nations having the highest patronage. The hazardous consequences of this quantity on human and animal health are enormous and a matter of urgent public health concern. This work is aimed at determining the effect of dichlorvos-treated bean diets on immune profiles and the structural integrity of the spleen in rats. A total of twenty-eight (28) kilograms of bean (Phaseolus vulgaris) was acquired and divided into seven groups of 4kg each. Group I is the control group and did not receive any dichlorvos treatment. Groups IIa, IIb, and IIc only received high, medium, and low doses respectively while groups IIId, IIIe and IIIf received high, medium, and low doses of dichlorvos respectively thereafter parboiled and dried. All samples were stored for six months, separately ground into powder form using a blender then mixed with rat feed and fed to the rats for thirty days. At the end of the treatment, the rats were anaesthetized with chloroform, and blood samples were collected through cardiac puncture for determination of white blood cell profile. The spleen was harvested and preserved in 10% formaldehyde for histological analysis. The result showed that in groups IIa, IIb, and IIc all the immuno-protective components of the cell increased significantly when compared to the control. Cross-examination of the spleen showed various degrees of structural abnormalities caused by dichlorvos.